Trichoderma-Induced Acidification Is an Early Trigger for Changes in Arabidopsis Root Growth and Determines Fungal Phytostimulation - Pelagio-Flores, Ramón; Esparza-Reynoso, Saraí; Garnica-Vergara, Amira; López-Bucio, José; Herrera-Estrella, Alfredo (Frontiers in Plant Science, 2017)
Trichoderma spp. are common rhizosphere inhabitants widely used as biological control agents and their role as plant growth promoting fungi has been established. Although soil pH influences several fungal and plant functional traits such as growth and nutrition, little is known about its influence in rhizospheric or mutualistic interactions. The role of pH in the Trichoderma–Arabidopsis interaction was studied by determining primary root growth and lateral root formation, root meristem status and cell viability, quiescent center (QC) integrity, and auxin inducible gene expression. Primary root growth phenotypes in wild type seedlings and STOP1 mutants allowed identification of a putative root pH sensing pathway likely operating in plant–fungus recognition. Acidification by Trichoderma induced auxin redistribution within Arabidopsis columella root cap cells, causing root tip bending and growth inhibition. Root growth stoppage correlated with decreased cell division and with the loss of QC integrity and cell viability, which were reversed by buffering the medium. In addition, stop1, an Arabidopsis mutant sensitive to low pH, was oversensitive to T. atroviride primary root growth repression, providing genetic evidence that a pH root sensing mechanism reprograms root architecture during the interaction. Our results indicate that root sensing of pH mediates the interaction of Trichoderma with plants.